Peningkatan Kompetensi Mahasiswa Sosiologi Dalam Analisis Masalah Sosial Pekerja Anak Pada Mata Kuliah Sosiologi Industri Melalui Metode Pembelajaran Inkuiri Sosial - Oryza Pneumatica Inderasari (Universitas Mataram, 2021)
This study aims to develop and improve students' abilities in analyzing using a sociological perspective and providing recommendations for solving social problems, especially regarding child labor. The research subjects were students of Industrial Sociology, Unram Study Program of Sociology. Industrial Sociology learning on the subject of Industry and family with a focus on the theme of Child Labor studies invites students to be actively involved in finding and solving social problems in the industrial sector. Trying to explain that members of lower socio-economic families who have potential as workers are involved in business activities carried out by the family or called home industry as well as fields of work run by parties other than the nuclear family. The consequence of the need to fulfill daily living expenses is that adults allow children to work, even coercion and other forms of exploitation occur in the world of child labor. The Lewis Learning Model is used to analyze the focus of the theme, while the evaluation of a series of learning activities is carried out by action research. In the results and discussions, articles that resulted from thinking together with lecturers and students were presented on related themes. From this learning process, it can be concluded that students are able to attend lectures well, meet the final abilities of learning on the subject of Industry and Family and support the learning outcomes of Industrial Sociology courses comprehensively